CTNI-35. PHASE 0/1 TRIAL OF MYCOPHENOLATE MOFETIL COMBINED WITH CHEMORADIATION TO OVERCOME TREATMENT RESISTANCE IN NEWLY DIAGNOSED AND RECURRENT GLIOBLASTOMA BY TARGETING PURINE METABOLISM. (14th November 2022) - Umemura, Yoshie; Al-Holou, Wajd; Marini, Bernard; Leung, Denise; Kim, Michelle; Ferris, Sean; Junck, Larry; Sagher, Oren; Heth, Jason; Sun, Yilun; Schipper, Matthew; Lyssiotis, Costas; et al.
Abstract: BACKGROUND: Purine metabolism promotes glioblastoma growth, stemness, invasiveness, and treatment resistance. The purine synthesis inhibitor, mycophenolate mofetil (MMF), improves radiation and temozolomide efficacy in preclinical glioblastoma models. This phase 0/1 trial (NCT04477200) aims to determine the maximum-tolerated dose of MMF combined with chemoradiation in glioblastoma. It also aims to quantify the levels of the active metabolite of MMF and the extent of purine synthesis inhibition in enhancing and non-enhancing tumor tissue. METHODS: Key eligibility criteria are age ≥ 18 and KPS ≥ 60%. TITE-CRM dose-escalation is used for MMF dosing starting at 1000mg PO BID (range 500-2000mg BID). Thirty recurrent glioblastoma patients receive MMF one-week prior to and concurrently with re-irradiation (40.5 Gy in 15 fractions), with 28 days of dose-limiting toxicity (DLT) period. Thirty newly diagnosed glioblastoma patients receive MMF one-week prior to and concurrently with standard radiation with concurrent temozolomide and followed for 28 days for DLT1-period, then MMF is given days 0-5 of each adjuvant cyclic temozolomide using a separate dose-escalation with the first two cycles as the DLT2-period. In phase 0, eight recurrent glioblastoma patients receive MMF 500-2000mg PO BID one-week pre-operatively and tissues are analyzed using mass spectrometry. RESULTS: Eighteen phase 1 subjects (11 recurrent, 7 new) have received study treatment with no DLT to date up to MMF 2000mg BID. Main toxicities are mild nausea, fatigue, and elevated liver enzymes. No notable study-related hematotoxicity nor opportunistic infection have been observed. The active metabolite of MMF accumulated to active concentrations in enhancing and non-enhancing tumor tissue and appeared to inhibit purine synthesis. CONCLUSION: MMF combined with chemoradiation has been reasonably well tolerated in glioblastoma patients with preliminary evidence of intracranial target engagement of its active metabolite. This study will yield a recommended phase 2 dose and preliminary efficacy estimate for future randomized phase 2/3 trial.